Differences of Acceptability and Candied Water Content of Pamelo Orange Albedo Soaked in Red Roselle Solution with Commercial Products - Iga Ayu Lestari (Universitas Muhammadiyah Sidoarjo, 2020)
Pamelo orange albedo is an orange peel which is white colored inside and can be used as food processing, one of which is dried candied. Roselle contains anthocyanin pigments which can be used as natural red coloring in the process of making pamelo orange albedo candied. The treatment product of red roselle albedo candied through an soaking process on a 10% red roselle petal solution. This immersion is intended for the provision of natural red coloring, while there is a content of vitamin C and citric acid to help bring the sensation of a natural sour taste typical of candied. This study aims to determine differences of red roselle petal albedo candied with commercial products that are analyzed in computerized way. The acceptability testing uses Mann Whitney test, while water content testing uses T-Test. Results of the study showed that there was a difference in the color acceptability of pamelo orange albedo candied which was soaked in a solution of red roselle petals with commercial products, but there was no difference in the acceptability of aroma, texture, taste, and water content. Selected products in terms of color, aroma, and texture were on candied commercial pamelo albedo candied. Meanwhile, in terms of taste, the selected products were the treatment products because there was a natural sour taste typical of red roselle petals. Commercial products had a water content of 16.5%, while the treatment product was 18.5%. SNI No. 1718 (1996), the maximum limit of water content in candied is 25%. There needs to be an improvement in the acceptability of the treatment products in terms of soaking the solution of red roselle petals and drying of albedo candied.